Pengaruh Store Atmosphere, Food Quality, dan Service Quality terhadap Revisit Intention pada Pelanggan Korean Garden Thematic Cafe: Studi pada Rest Korean Garden Coffee And Eats Sidoarjo - Afida Rossa, Zirli; Respati Kusumasari, Indah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
In recent years, many café businesses in the city of Sidoarjo have started to apply certain themes to attract consumers to visit, one of which is Rest Korean Garden Coffee and Eats Sidoarjo which applies the theme of Korean garden café. On the other hand, the café business must have advantages including the café atmosphere, the quality of food, and the quality of service aimed at making customers visit again. This study aims to analyze the effect of store atmosphere, food quality, and service quality on revisit intention in customers of Rest Korean Garden Coffee and Eats Sidoarjo in the midst of many cafes that have begun to apply the concept of themed cafes. The population used in this study was customers of Rest Korean Garden Coffee and Eats Sidoarjo with a total sample of 170 respondents determined based on purposive sampling. The method used is quantitative through the distribution of questionnaires with Likert scale measurements. The results showed that partially and simultaneously, store atmosphere, food quality, and service quality had a significant effect on revisit intention.